Unfired clayey pellets as the adsorbents for metal ions removal from a waste printing developer - Kiurski Jelena; Ranogajec Jonjaua; Kecić Vesna; Oros Ivana; International Symposium on Analytical and Environmental Problems (21.) (2015) (Szeged) (2015)
The paper analyses the application of various forms of unfired clay pellets (whole and half), for the removal of zinc and copper ions from a waste printing developer. The adsorption experiments were performed in batch mode. The textural properties of defined clayey pellets were examined by mercury porosimetry. Textural characterization showed a significant amount of the small pores in the case of whole pellets in relation to half pellets. The efficiency of the metal ions removal significantly increases with the increase of the adsorbents mass. The removal efficiency varied between 50 and 94%. Considering the adsorption efficiencies, the following order of unfired clay pellets was noticed: whole pellet > half-pellet. The ionic radius of metal ions and the obtained trends of adsorption efficiency show that the selectivity sequence of metal ions on the unfired clay pellets was Zn > Cu. Therefore, the unfired clayey adsorbents present the promising alternatives for purification of waste printing developers.